ON THE PERSONAL FACTOR IN THE LANGUAGE SYSTEM (Universal International Scientific Journal, 2026)
This article examines the role and significance of the personality factor in the language system within the framework of modern linguistic paradigms. The study sheds light on the essence of language as a complex social, cognitive and cultural phenomenon based on an anthropocentric approach. The inextricable link between the language system and the individual is analyzed from the perspective of linguistic semantics, cognitive linguistics, psycholinguistics, pragmalinguistics and linguoculturology. The article reveals the evolution of language paradigms, in particular, the relationship between comparative-historical, system-structural and anthropocentric paradigms. The theoretical views of such scientists as N. Chomsky, V. von Humboldt, Y. S. Stepanov, N. Mahmudov are used to study the formation of language in the human mind, its manifestation in speech activity and the features of reflecting cultural codes. The results of the study show that the study of the language system in isolation from the human factor is limited, while the anthropocentric approach reveals the essence of language more deeply. The article is of theoretical and methodological importance for modern linguistic research.
Keywords: language system; personality; anthropocentric paradigm